Large parametric change-point detection by a V-box control chart. Issue 2 (2nd April 2016) - Furmańczyk, Konrad; Jaworski, Stanisław
ABSTRACT: A new method of detecting a change in a sequence of independent observations is presented. The method is based on the concept of a moving vertically trimmed box and a minimax decision rule. This approach takes into account the admissible level of the change.